Dakwah Kultural sebagai Wujud Moderasi Beragama: Studi pada Masyarakat Desa Tajau Pecah Kalimantan Selatan - Nida Nabighah Qurrata’ayun; Ilham Ilham; Ermalianti Ermalianti (ANWARUL, 2025)
Amid the ethnic, religious, and cultural diversity of Tajau Pecah Village, Batu Ampar Subdistrict, Tanah Laut Regency, conventional forms of dakwah potentially face challenges in fostering religious moderation. This study aimed to analyze the forms of cultural dakwah practiced in Tajau Pecah Village and to explain how the values of religious moderation are integrated into local cultural traditions. The research employed a descriptive qualitative approach, with data collected through observations and interviews with the residents of Tajau Pecah Village and subsequently analyzed thematically. The findings show that cultural dakwah is manifested through the traditions of Baaruahan, Batapung Tawar, Brokohan, and Sepasaran, which effectively internalize the values of religious moderation, such as tolerance, openness to dialogue, and respect for differences. These results affirm that cultural dakwah grounded in local wisdom plays a crucial role in strengthening social harmony and community unity, and contributes to the designation of Tajau Pecah Village as a Kampung Moderasi Beragama (Religious Moderation Village). The implications of this study highlight the need to strengthen and replicate cultural dakwah models based on local traditions as a strategy for developing religious moderation in other multicultural areas.